2006
DOI: 10.1161/01.hyp.0000209340.33592.50
|View full text |Cite
|
Sign up to set email alerts
|

Brachial Blood Pressure But Not Carotid Arterial Waveforms Predict Cardiovascular Events in Elderly Female Hypertensives

Abstract: Abstract-Central arterial waveforms and related indices of large artery properties can be determined with relative ease.This would make them an attractive adjunct in the risk stratification for cardiovascular disease. Although they have been associated with some classical risk factors and the presence of coronary disease, their prospective value in predicting cardiovascular outcomes is unknown. The present study determined the relative predictive value for cardiovascular disease-free survival of large artery p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
110
6
18

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 57 publications
5
110
6
18
Order By: Relevance
“…12,13 McEniery et al 22 suggested that pressure wave analysis might be a more sensitive marker of CV risk in younger subjects than in older subjects, and the ANBP2 study reported that central BP is not an independent variable to predict future CV events in elderly women. 23 The results of the present study were consistent with the previous findings, indicating that SBP2 is useful in identifying not only high CV risk state but also low CV risk state in younger subjects. Table 3 Results of logistic regression analysis without and with adjustments to assess the significance of the second peak of the radial systolic pressure waveform for the identification of subjects with high and low CHD risk and high and low CVDgen risk Abbreviations: brSBP, brachial systolic blood pressure in the left upper arm determined using an oscillometric method; CHD, coronary heart disease; CI, confidence interval; CVDgen, general cardiovascular disease;Model 1 adOdds, odds ratio adjusted of the covariates in model 1 (the details are described in the footnote of Table 2); Model 2 adOdds, odds ratio obtained by the second peak of the radial systolic pressure waveform, the brachial systolic blood pressure and the covariates in model 1 were entered simultaneously into the model; SBP2, second peak of the radial systolic pressure waveform.…”
Section: Discussionsupporting
confidence: 92%
“…12,13 McEniery et al 22 suggested that pressure wave analysis might be a more sensitive marker of CV risk in younger subjects than in older subjects, and the ANBP2 study reported that central BP is not an independent variable to predict future CV events in elderly women. 23 The results of the present study were consistent with the previous findings, indicating that SBP2 is useful in identifying not only high CV risk state but also low CV risk state in younger subjects. Table 3 Results of logistic regression analysis without and with adjustments to assess the significance of the second peak of the radial systolic pressure waveform for the identification of subjects with high and low CHD risk and high and low CVDgen risk Abbreviations: brSBP, brachial systolic blood pressure in the left upper arm determined using an oscillometric method; CHD, coronary heart disease; CI, confidence interval; CVDgen, general cardiovascular disease;Model 1 adOdds, odds ratio adjusted of the covariates in model 1 (the details are described in the footnote of Table 2); Model 2 adOdds, odds ratio obtained by the second peak of the radial systolic pressure waveform, the brachial systolic blood pressure and the covariates in model 1 were entered simultaneously into the model; SBP2, second peak of the radial systolic pressure waveform.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, in the ANBP2, central BP was estimated by carotid applanation tonometry. 10,15 Interestingly, in the current study by Dart et al, 10 brachial pulse pressure tended to be equal or even lower than central pulse pressure, which may raise concern and certainly fuels debate on the reliability of those measurements. On the other hand, on a theoretical basis, it may be argued that the radial applanation tonometry detects a difference between central and peripheral BP, because it extrapolates central BP by the transfer function 13 in which a difference between the 2 BPs is built in.…”
contrasting
confidence: 50%
“…10 Furthermore, the study by Dart et al 10 is based on a pairwise design, whereas the CAFE Study 6 included patients who reached end points. Previously, Dart et al 15 showed that brachial, and not central, BP was related to total fatal and nonfatal cardiovascular events in the ANBP2; therefore, the authors commented that the pairwise design did not introduce significant survival effects in the present ANBP2 substudy. 10 Notwithstanding, in the present ANBP2 substudy, 10 the lack of difference in outcome by study design between the treatment arms might have selected negatively those at higher risk of fatal cardiovascular events because of higher central BP.…”
mentioning
confidence: 66%
“…Another limitation of this study is that brachial SBP and DBP were used to calculate the carotid CSDC and stiffness β instead of carotid SBP and DBP, respectively. Physiologically, mean blood pressure and DBP are nearly identical in the carotid and brachial arteries, whereas SBP and pulse pressure are significantly higher in the brachial arteries than the carotid arteries, although the differences are minimized with aging (31). This may be a reason that CAVI was associated with stiffness β and CSDC, although these associations were relative weak.…”
Section: Discussionmentioning
confidence: 99%